Comparative study of adsorptions, reactions and electronic properties of U atoms on Cu(111), Ag(111), Au(111) and Ru(0001) surfaces. (29th July 2021) - Feng, Wei; Hao, Qunqing; Chen, Qiuyun; Qiu, Ruizhi; Lai, Xinchun; Chen, Jinfan; Liu, Qin
Abstract: The mysterious properties of individual U atoms on transition metal surfaces play indispensable parts in supplementing our understanding of uranium-transition metal systems, which are important subjects for both nuclear energy applications and fundamental scientific studies. By using scanning tunneling microscopy and density functional theory calculations, the adsorptions, reactions and electronic properties of individual U atoms on Cu(111), Ag(111), Au(111) and Ru(0001) surfaces were comparatively studied for the first time in this work. Upon the deposition of a small amount of U onto Cu(111) or Ag(111) at 8 K, individual U atoms show relatively high activity and can either be adsorbed on intact substrate surfaces or induce various surface vacancies surrounded by clusters of substrate atoms. By contrast, the majority of U atoms tend to dispersedly adsorb on intact surfaces of Au(111) and Ru(0001) rather than producing surface vacancies at the same temperature. In all cases, Kondo resonance manifested as asymmetric dip feature around Fermi energy is only observed in the differential tunneling conductance spectra of single U adatoms on Ag(111).